(untitled) (Dhaka University Journal of Biological Sciences, 2020)
Three antagonistic fungi were isolated from the field soil of blight infected Tagetes spp. by serial dilution method. The fungi were identified as Aspergillus flavus Link, A. niger van Tiegh. and Trichoderma viride Pers. Antagonistic potentiality of aforesaid fungi were evaluated against the pathogenic fungi of Tageteserecta L. and T. patula L. following "dual culture colony interaction" and volatile and nonvolatile metabolites. The pathogenic fungi were A. alternata, Aspergillus fumigatus and Curvularia lunata. In dual culture colony interaction, out of three soil fungi, T. viride showed the highest growth inhibition on A. alternata (71.03%), A. fumigatus (38.49%) and C. lunata (60.71%). The maximum inhibition of radial growth of A. alternata (74.55%) was observed with the culture filtrates of T. viride owing to volatile metabolites. The maximum inhibition of radial growth of A. fumigatus (37.43%) was observed with the culture filtrates of A. flavus owing to volatile metabolites. The complete inhibition of radial growth of C. lunata was observed with the culture filtrates of A. niger owing to volatile metabolites. The complete inhibition of radial growth of A. alternata was observed with nonvolatile metabolites of A. nigera and T. viride at all concentrations. The complete inhibition of radial growth of A. fumigatus was also observed with nonvolatile metabolites of A. niger at all concentrations. Aspergillus niger and T. viride may be exploited commercially as a biocontrol agent against blight pathogens of T. erecta and T. patula. Dhaka Univ. J. Biol. Sci. 29(2): 147-153, 2020 (July)